2012
DOI: 10.1107/s0108768111051639
|View full text |Cite
|
Sign up to set email alerts
|

Water channel structure of bassanite at high air humidity: crystal structure of CaSO4·0.625H2O. Corrigendum

Abstract: The correspondence author in the paper by Schmidt et al. [(2011), Acta Cryst. B67, 467–475] is corrected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…We can cite, as an example, the case of the CaSO 4 · n H 2 O compounds for which controversial discussions occurred about the true crystal structure (hexagonal or not) and the role of the water amount inside the channels. It was finally shown that CaSO 4 ·0.5H 2 O crystallizes in a C 2 space group, while the CaSO 4 ·0.625H 2 O , crystallizes in a P 3 2 21 space group by doubling the original hexagonal unit cell parameters. However, both structures derivate from the original hexagonal model, , but differ markedly in terms of the water molecules arrangement.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We can cite, as an example, the case of the CaSO 4 · n H 2 O compounds for which controversial discussions occurred about the true crystal structure (hexagonal or not) and the role of the water amount inside the channels. It was finally shown that CaSO 4 ·0.5H 2 O crystallizes in a C 2 space group, while the CaSO 4 ·0.625H 2 O , crystallizes in a P 3 2 21 space group by doubling the original hexagonal unit cell parameters. However, both structures derivate from the original hexagonal model, , but differ markedly in terms of the water molecules arrangement.…”
Section: Resultsmentioning
confidence: 99%
“…However, from the synthesis point of a view, the control of the amount of the water molecules inside the channels seems to be difficult so far. However, it could be possible during the dehydration and/or the rehydration steps or also by varying the relative humidity as shown by Schmidt et al in the case of the CaSO 4 ·0.5H 2 O. , The stabilization of the rhabdophane compounds by precipitation in aqueous solution represents a reliable procedure leading to pure phases with a variety of textural and microstructural properties. Moreover, it is in agreement with the different observations found in nature. ,,, …”
Section: Resultsmentioning
confidence: 99%